The Financial Channel of the Exchange Rate and Global Trade - Ma, Sai; Schmidt-Eisenlohr, Tim (Review of Financial Studies, 2025)
Abstract This paper provides evidence that the U.S. dollar affects trade through a financial channel of the exchange rate. Using global data over three decades, we show that dollar appreciation increases import prices and decreases import quantities for non-U.S. dollar countries. In line with a financial channel, these effects are stronger when the exporting country borrows more in U.S. dollars abroad. The financial channel was active before the global financial crisis, has strengthened since, and operates independently of the dominant currency invoicing channel. Instrumenting the dollar is key to uncovering the full effect of the financial channel.